Historical ecology: past, present and future - Szabó, Péter (Biological reviews of the Cambridge Philosophical Society, 2015)
The term 'historical ecology' has been used with various meanings since the first half of the 20th century. Studies labelled as historical ecology have been produced in at least four academic disciplines: history, ecology, geography and anthropology. Although all those involved seem to agree that historical ecology concerns the historical interconnectedness of nature and human culture, this field of study has no unified methodology, specialized institutional background and common publication forums. Knowledge of the development of historical ecology is also limited. As a result, the current multitude of definitions of historical ecology is accompanied by divergent opinions as to where the origins of the field are to be sought. In this review, I follow the development of historical ecology from the 18th century to the present. In the first part, I briefly describe some early examples of historical ecological investigations, followed by a description of the various scientific strands in the 20th century that contributed to the formation of historical ecology. In the second part, I discuss the past five decades of historical ecological investigations in more detail, focusing mostly (but not exclusively) on works that their respective authors identified as historical ecology. I also examine the appearance and interconnectedness of the two main trends (ecological and anthropological) in historical ecological research. In the last part, I attempt to outline the future of historical ecology based on common features in existing research. It appears that at present historical ecology is at a crossroads. With rapidly growing interest in historical ecological research, it may move towards institutionalization or remain an umbrella term.
Keywords: Ecology; dějiny 18. století; History, 21st Century; Humans; History, 19th Century; zvířata; dějiny 20. století; anthropology; History, 20th Century; dějiny 19. století; dějiny 21. století; human-nature interactions; Geography; zeměpis; interdisciplinarity; History, 18th Century; zachování přírodních zdrojů; historical ecology; Animals; lidé; environmental history; Conservation of Natural Resources; ekologie